Số số hạng là :
(52 + x) - (2 + x) : 2 + 1 = 26 (số hạng)
Tổng trên là :
[(52 + x) + (2 + x)] x 26 : 2 = (54 + 2x) x 26 : 2 = 780
=> (54 + 2x) x 26 = 1560
=> 54 + 2x = 60
=> 2x = 6
=> x = 3
( 2+x ) + (4+x ) + ( 6+x) + ....+ ( 52+x) = 780
Có tất cả các số x là :
(52 - 2) : 2+1= 26 (số)
Ta có :
X x26 + (2+ 4 +6 +....+52) = 780
X x 26+ 702 =780
X x 26 =780 - 702
X x 26 =78
X = 78 : 26
X = 3
Đáp số : 3
Số số hạng là :
(52 + x) - (2 + x) : 2 + 1 = 26 (số hạng)
Tổng trên là :
[(52 + x) + (2 + x)] x 26 : 2 = (54 + 2x) x 26 : 2 = 780
=> (54 + 2x) x 26 = 1560
=> 54 + 2x = 60
=> 2x = 6
=> x = 3